The Six-Minute Walking Exercise on The Fatigue Levels in Hemodialysis Patients - Yohanes Gamayana Trimawang Aji; Krisna Yetti; Lestari Sukmarini (Pusat Unggulan Iptek (PUI) Poltekkes Kemenkes Yogyakarta, 2020)
Patients undergoing routine hemodialysis are often experiencing fatigue. One of the interventions was made to minimize the level of fatigue through the six-minute walking exercise. This study aims at investigating the effectiveness of the six-minute walking exercise on the decreasing level of fatigue in patients undergoing hemodialysis. The method used is quasi-experiment with pretest-posttest control group design. Sixteen HD patients were recruited into two groups: the exercise training group (n= 8) and the control group (n= 8). The six-minutes walking was conducted in March - April 2017 in the hemodialysis room of Fatmawati Hospital Jakarta. Results indicated a significant decrease in fatigue level in the intervention group after four six-week walking exercises over a 2-week period. This is evidenced in the intervention group, there is a decrease in fatigue level from the category of moderate fatigue to mild fatigue. Six-minute walking exercise can be applied and developed by nurses as a part of a health education program to decrease fatigue levels in patients undergoing hemodialysis.